Prevalence and Risk Factors of Domestic Violence during Pregnancy: A Meta-Analysis Approach - Noorulain Javed, Saleem Ahmad, Shumaila Nargus, Muhammad Azizullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Domestic violence is of various types and is associated with various health risks. This also effects fetal health. Aim: To evaluate the prevalence and risk factors of domestic violence during pregnancy in Pakistan and other international settings. Methods: Material was taken through several search engines such as Google scholar, Medline and web search. Data is collected mostly from those studies which are carried out after year 2000. It includes observational studies reporting estimates of prevalence and its risk factors among pregnant women of age more than 15 years. For this purpose 6431 papers were screened and 41 papers met inclusion criteria. Results: Total 115506 participants from all over the world were represented in the data. Meta-analysis produced pooled prevalence estimates of lifetime exposure to any type of domestic violence (DV) of 46.546 % (95% CI 46.258-46.834) by fixed effect and by applying random effect prevalence of domestic violence is 35.349 % (95%CI 28.972-42.000). Conclusion: Domestic violence is common among females with low education. In this meta-analysis, lowest prevalence of domestic violence in pregnant females is come out in Japan and highest in third world countries like Ethiopia, Africa. Keywords: Domestic violence, intimate partner violence, prevalence, Pregnancy, Pakistan